Female madness between mythical and medical tradition - Carra, Esther (Myrtia, 2024)
The aim of this article is to analyze how female madness is placed between mythical and medical tradition. Medical sources recognize and treat mental illness, the etiology of which is sought in a physical place of the body and always associated with the functioning of the uterus, so much so that it is perceived as an object of integration into society. According to the doctors of the Corpus Hippocraticum, an interaction between body and psyche generates psychic affections, that is signs of a biological imbalance. The pathologies of the uterus can be solved with sexual activity and with pregnancy: an example can be found in Girls, the Hippocratic treatise examined. The mythical sources foresee an ethical sanction that leads to considering madness as an object of segregation and isolation. In this regard, three myths are examined: Io in Aeschylus’ Prometheus Bound, Phaedra in Euripides’ Hippolytus and Agave in Euripides’ Bacchae. In each case, the madness of these three women is caused by a deity. Although the characters concerned are innocent, their insanity causes a violation of ethical values. A particular case is the myth of the Proetides, in which the young women unleash divine wrath and the consequent punishment. Proetus’s daughters are healed and, finally, through marriage, they respect the representations and beliefs relating to the role of young women within Greek society.